2012
DOI: 10.1038/eye.2012.230
|View full text |Cite
|
Sign up to set email alerts
|

5 Years review of periocular basal cell carcinoma and proposed follow-up protocol

Abstract: In all, 67% were nodular BCC and 45.4% located in the lower eyelid. The main outcome measure was the recurrence rate. None of the patients with primary nodular BCC suffered recurrence. The recurrence rate for primary morphoeaform BCC following complete excision is 3.8%. In total, 8.1% of patients had several lesions simultaneously whereas 7.8% patients had BCC in multiple locations subsequently (metachronous). Three patients who had previously recurrent BCC (rBCC) treated elsewhere or not using this method had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 42 publications
(44 reference statements)
6
37
2
1
Order By: Relevance
“…Additionally, latitude has been shown to influence BCC subtype more than body site, with significantly higher proportions of infiltrative and superficial BCC found on the head and neck in the Townsville study compared with in the periocular region in the United Kingdom study. 7,11 Our findings are in keeping with this, as we reported higher proportions of infiltrative and superficial BCC compared with studies of head and neck BCC conducted at higher latitudes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Additionally, latitude has been shown to influence BCC subtype more than body site, with significantly higher proportions of infiltrative and superficial BCC found on the head and neck in the Townsville study compared with in the periocular region in the United Kingdom study. 7,11 Our findings are in keeping with this, as we reported higher proportions of infiltrative and superficial BCC compared with studies of head and neck BCC conducted at higher latitudes.…”
Section: Discussionsupporting
confidence: 79%
“…Our study demonstrated higher rates of infiltrative BCC compared with superficial subtype, consistent with previous reports from Townsville, Brisbane and the United Kingdom of facial and periocular BCC. 7,11,12 These findings may be attributable to the theory which suggests that superficial BCC results from acute, intense sun exposure to skin that is less exposed to sunlight and thus less tanned.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This finding is particularly constant with previous study in Oradea while interestingly, most other studies describing nodular BCC as the most common histological type. 2,6,9,11 There are limitations in this study where this study may not represent the entire Bandung population. Nonetheless, this study provides a compelling overview of BCC as a basis of upcoming research and essential information for physicians and the community.…”
Section: Discussionmentioning
confidence: 99%